Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure, let's solve for [tex]\( f(-3) \)[/tex] and [tex]\( g(-2) \)[/tex] using the given functions step-by-step.
Starting with [tex]\( f(x) = 5x + 4 \)[/tex]:
1. To find [tex]\( f(-3) \)[/tex], substitute [tex]\( x = -3 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(-3) = 5(-3) + 4 \][/tex]
2. Now, calculate the value:
[tex]\[ f(-3) = -15 + 4 \][/tex]
3. Simplify the expression:
[tex]\[ f(-3) = -11 \][/tex]
Next, for [tex]\( g(x) = 3x^3 + 5 \)[/tex]:
1. To find [tex]\( g(-2) \)[/tex], substitute [tex]\( x = -2 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(-2) = 3(-2)^3 + 5 \][/tex]
2. Now, calculate the value of [tex]\((-2)^3\)[/tex]:
[tex]\[ (-2)^3 = -8 \][/tex]
3. Substitute back into the function:
[tex]\[ g(-2) = 3(-8) + 5 \][/tex]
4. Calculate the resulting value:
[tex]\[ g(-2) = -24 + 5 \][/tex]
5. Simplify the expression:
[tex]\[ g(-2) = -19 \][/tex]
So, the solutions are:
[tex]\[ f(-3) = -11 \][/tex]
[tex]\[ g(-2) = -19 \][/tex]
Starting with [tex]\( f(x) = 5x + 4 \)[/tex]:
1. To find [tex]\( f(-3) \)[/tex], substitute [tex]\( x = -3 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(-3) = 5(-3) + 4 \][/tex]
2. Now, calculate the value:
[tex]\[ f(-3) = -15 + 4 \][/tex]
3. Simplify the expression:
[tex]\[ f(-3) = -11 \][/tex]
Next, for [tex]\( g(x) = 3x^3 + 5 \)[/tex]:
1. To find [tex]\( g(-2) \)[/tex], substitute [tex]\( x = -2 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(-2) = 3(-2)^3 + 5 \][/tex]
2. Now, calculate the value of [tex]\((-2)^3\)[/tex]:
[tex]\[ (-2)^3 = -8 \][/tex]
3. Substitute back into the function:
[tex]\[ g(-2) = 3(-8) + 5 \][/tex]
4. Calculate the resulting value:
[tex]\[ g(-2) = -24 + 5 \][/tex]
5. Simplify the expression:
[tex]\[ g(-2) = -19 \][/tex]
So, the solutions are:
[tex]\[ f(-3) = -11 \][/tex]
[tex]\[ g(-2) = -19 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.